AN OBSERVATIONAL STUDY TO ASSESS THE CLINICAL-ETIOLOGICAL PROFILE OF HYPONATREMIA IN PATIENTS PRESENTING TO THE EMERGENCY DEPARTMENT IN A TERTIARY CARE HOSPITAL. - Namrata Mathur; Jiss Peter; Kapil Dev Mathur; Sanjukta Dutta; Sucharita Chakravarti (Student’s Journal of Health Research Africa, 2024)
Background When the serum sodium level is less than 135 mmol/l, it is called hyponatremia. It may show a range of symptoms, including nausea, tiredness, seizures, coma, and sometimes even death. If identified immediately, proper treatment can reduce these symptoms and fatality rates. This study assessed the clinical characteristics and underlying causes of hyponatremia in admitted patients. Materials and Methods This study was observational. Patients who were at least 14 years old and had serum Na+ levels ≤130 meq/l were included in the study. Patients were diagnosed as having hypovolemic hyponatremia, hypervolemic hyponatremia, or euvolemic hyponatremia based on the results of their medical histories and physical examinations. The syndrome of inappropriate antidiuresis (SIAD) was identified in patients with clinical euvolemia, urine Na+ >20 mmol/l, serum uric acid ≤4 mg/dl, satisfactory renal function (serum creatinine and blood urea), and no pituitary or thyroid disease. Results The study comprised 100 individuals with hyponatremia. 56 individuals had severe hyponatremia. 38 patients experienced vomiting, 7 experienced hiccups, 19 hyponatremic patients were asymptomatic, and 43 patients had altered levels of consciousness manifested as sleepiness, disorientation, irrelevant talking, or coma. Euvolemic hyponatremia (71%) was the most common, followed by hypervolemic hyponatremia (27%), and hypovolemic hyponatremia (2%). Conclusion Ages 60 to 69 were the most common range for hyponatremia. The majority of patients belonged to the hypervolemic category after the euvolemic group. The most typical signs of hyponatremia were impaired sensorium, vomiting, and, infrequently, seizures. Recommendation Diuretics should be used with caution, especially in more vulnerable groups, as they often result in hyponatremia. Diuretic-induced hyponatremia may occur, but additional factors, including the patient’s euvolemic status, should be considered to prevent it from always turning hypovolemic. The intensity of the symptoms should be given priority over serum salt levels, as there is no correlation between them.